Narrativas orais da cidade de Lucena-PB: influências nas práticas discursivas nas aulas de língua portuguesa com estudantes da 3ª série do ensino médio - Gomes, Maria José Davi (2023)
In the present research we propose as objectives to analyze the influences of oral narratives from the city of Lucena-PB in the discursive practices of the students of the 3rd Grade of High School. And, more specifically: a) Investigate the linguistic and discursive elements of orality present in the students' narratives; b) understand the relationship and difference between oral and written discourse in Portuguese language teaching; c) realize that oral tradition is established by historical, cultural and social change; d) present the students' linguistic conceptions used in the analysis. This study is justified because it is a region that is characterized by the presence of oral culture still exerting a very strong influence on the community, however, there are no studies with the thematic focus of oral narratives and their contributions in Portuguese Language classes in high school, which can help public education in the city and improve students' communication, as well as contributions regarding the teaching of orality in Portuguese language classes in high school. From this investigative linguistic perspective, we follow as a guideline for the theoretical framework the study of the respective scholars: Bakhtin (1992), Marcuschi (2001, 2003, 2010), Geraldi (2000-2006), Aquino (2005), Castilho (1998), Fávero (2005), Bagno (1999), Ecléa Bosi (1994), Maurice Halbwachs (1990), Castilho (1998), Galvão (2015), Maingueneau (2001), among others. The methodological procedures were based on action-research, of a qualitative and participative nature through interpretative analysis, the instruments used were: 1) Interview with 10 collaborating students; 2) Field diary and observation of the school environment in 8 Portuguese classes; 3) Visits and holding a focus group with about 10 students participating in 3 meetings; 4) Analysis of the activities carried out in this class in comparison with what was said during the interviews and focus groups, opening space for discussions and investigations on the subject addressed. The general results of the research point to the students' collaboration so that we could somehow show that oral narratives exert influence in the community, and that most recognize that these narratives are in fact passed on orally, especially by the elderly, being part of the culture local, recognizing the importance of developing linguistic competence, more precisely orality in their discursive practices.